Of an Age, Not Just for All Time: Shakespeare's Screen Traffic in a City and Time "Out of Joint". (3rd April 2021) - Ingham, Michael
ABSTRACT: This essay will assess the extent to which screened broadcasts of Shakespeare plays in Hong Kong contribute to a sense of cosmopolitan cultural identity in the city, and engage with current issues and events, as Shakespearean presentist theory argues. I will discuss how this relatively recent digitally mediated traffic in transnational Shakespeare, functioning as it does as a simulacrum of the physical theatre-going experience, resonates with the sociocultural ethos of Hong Kong. Like the asynchronous – as opposed to simulcast – theatre broadcast of Western Shakespeare, the time seems palpably "out of joint" to many residents of the city. A major factor affecting the continuation of Hong Kong's hitherto rich cultural life is the rapidly accelerating erosion of its autonomy and supposedly guaranteed civic freedoms, following Beijing's imposition of sweeping national security legislation. The essay discusses the significance of Shakespeare theatre broadcast in this highly charged political atmosphere in Hong Kong, with its dwindling, but stubbornly residual, cultural links to the country of the dramatist's birth. The second part will explore the local resonances of four broadcast theatre productions of Shakespeare plays in Hong Kong, Coriolanus and Hamlet (both NT Live) and The Tempest and Titus Andronicus (both RSC Live).